The need for special skills training in the last year of residency, with an emphasis on minimally invasive surgery - Muhammad Nauman; Mudassir Hussain; Asad Shahzad Hasan (Journal of the Pakistan Medical Association, 2025)
I am writing to address an important issue of minimally invasive surgery (MIS) training for surgical residents. The benefits of this kind of surgery have been well documented in the literature in the last decade, not only for patients but also for surgeons. Therefore, we must ensure our future surgeons are equipped with the skills necessary to deliver the best surgical outcomes. The transition to minimally invasive surgery (MIS) faces several challenges, including inadequate infrastructure, a shortage of trainers, high costs, and an outdated surgical curriculum. Despite MIS being practised in many major public sector tertiary hospitals in Pakistan, the lack of training resources can be addressed through the establishment of simulation centres for residents to improve their skills. The surgical training curriculum across all surgical specialties needs an urgent update to reflect the changing landscape of surgery. A focus on introducing minimally invasive surgery in the early years of training to achieve minimum necessary skills at the end of training is essential. Additionally, establishing dedicated fellowship programs to further enhance MIS skills will ensure more trainers are available to promote MIS in Pakistan. The integration of social media and web technologies in medical education presents an opportunity to facilitate the sharing of knowledge and collaboration among residents and faculty members [1]. These platforms can serve as effective tools for disseminating information, fostering collaboration, and supplementing traditional learning methods with self-directed learning opportunities [2]. The study highlights the necessity for specialized training in minimally invasive surgery during residency, demonstrating significant performance improvements among participants. However, only 10.7% felt fully capable of performing unsupervised low-complexity laparoscopic surgery post-training, indicating ongoing skill development needs. [3] Surgeon’s report feeling ill-equipped for independent minimally invasive surgery (MIS) oncology practice due to a lack of standardized training. This highlights the need for specialized skills training in the last year of residency to enhance proficiency in MIS techniques. [4] Inadequate MIS training in urology residency can escalate complications, as surgical success hinges on the surgeon’s expertise. Lack of training stifles the growth of vital laparoscopic skills for intricate operations. The calibre of MIS training in urology residency shapes surgeons’ prowess in minimally invasive techniques. Skill-based training fosters mastery, ensuring trainees hit targets before they operate, resulting in more assured and adept surgeons in the surgical arena [5]. —Continue